ANALYSIS OF THE DEVELOPMENT OF REGIONAL SOCIO-ECONOMIC CONDITIONS ON THE AGING POPULATION IN ACEH PROVINCE - Al Azizah, Rohil; Mulyani, Wiwik Puji; Sukamdi, Sukamdi (Jurnal Biometrika dan Kependudukan, 2024)
Socio-economic developments in Aceh Province have had a real impact which is reflected in the reduction in death and birth rates as well as an increase in life expectancy, causing changes in the composition of the population aged 60 years and over to increase. However, the developments that have occurred are not evenly distributed throughout the region, it is crucial to be aware of the concept of "being not ready to get old" that will arise in Aceh Province. This study analyzes the socio-economic development of regions with population aging in Aceh Province. The study was conducted with a quantitative approach. Data collection using documentation. Data analysis using descriptive analysis and modification of the Klassen typology. The results of the study showed that Aceh Province in 2020 was in the early aging stage (Mid-Aged) because the percentage of elderly people was more than 7%. It is estimated that in the next 25 years in 2035 Nagan Raya, South Aceh, and West Aceh will be in the high aging category (Super-Aged) or more than 14% and the results of the Klassen typology analysis using socio-economic indicators on population aging show that the development of the 23 districts/cities in Aceh Province is not only in areas that are high growth and high income (quadrant I), several districts/cities are in the category of low growth and low income (quadrant III)  where socio-economic development is low but have entered the early aging stage.